Giftedness and YouTube® livestream in the pandemic period: a systematic review - Rodrigues de Souza, Amanda; Santos de Oliveira, Ana Paula; de Araújo Rangni, Rosemeire (REDUFOR: revista Educação & Formação, 2024)
The livestreams became very popular during the pandemic period, with numerous invitations to broadcast on a wide variety of topics, including giftedness, leading academic interest in this new event format. Thus, this article aims to present what was broadcast in livestreams about giftedness during the pandemic period (2020-2022), on YouTube®, through a systematic review search. The results found were 22 videos related to more introductory themes to giftedness and other approaches, such as parenting, acceleration, mathematics, giftedness and autism, and over-excitability. To conclude, although the introductory themes to giftedness were more frequent, the livestreams played an important role of information for teachers and professionals to know the theme, even if previously.
Altas capacidades e as lives do YouTube® no período da pandemia: uma revisão sistemática
Altas capacidades y transmisiones en directo en YouTube® en el periodo pandémico: una revisión sistemática
As lives tornaram-se muito populares no período pandêmico, com numerosos convites para transmissões sobre os mais diversos temas, inclusive, sobre as altas capacidades, fazendo com que o interesse acadêmico se voltasse para esse novo formato de evento. Desse modo, este artigo se propõe a apresentar o que foi transmitido em lives sobre as altas capacidades durante o período da pandemia (2020-2022), no YouTube®, por meio de pesquisa sistemática. Os resultados encontrados foram 22 vídeos relacionados a temas mais introdutórios às altas capacidades e outras abordagens, como a parentalidade; a aceleração; a matemática; as altas capacidades e o autismo; e a sobre--excitabilidade. Conclui-se que, apesar de temas mais introdutórios às altas capacidades terem sido mais incidentes, as lives cumpriram importante papel de informação para docentes e profissionais conhecerem a temática, mesmo que previamente.
Keywords: live stream; giftedness; teacher training; YouTube livestreams; live; altas capacidades; formação docente; livesno YouTube; transmisiones en directo; altas capacidades; formación de profesores; transmisiones en directo en YouTube; JCR